2009
DOI: 10.1590/s0004-282x2009000200015
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy in children with fetal alcohol spectrum disorders

Abstract: -Objective: To analyze the metabolic constitution of brain areas through proton magnetic resonance spectroscopy in children affected with fetal alcohol spectrum disorder compared with normal children. Method: The sample of this case-control study included eight boys with epidemiologic history of in utero exposure to alcohol (median age 13.6±3.8 years) who were diagnosed with fetal alcohol spectrum disorder, and eight controls (median age 12.1±3,4 years). An 8 cm 3 single voxel approach was used, with echo time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
10
0
2
Order By: Relevance
“…Volume is not the sole attribute that can be measured of deep gray matter structures by using a variety of imaging methods. Magnetic resonance spectroscopy studies have reported altered brain metabolism in the thalamus (Fagerlund et al., 2006), striatum (Goncalves Rde et al., 2009), and caudate (Cortese et al., 2006) in FASD. Positron emission tomography revealed decreases in regional cerebral metabolic rates in bilateral thalamus and basal ganglia, which includes the caudate, putamen, and globus pallidus, in individuals with FAS (Clark et al., 2000) and single‐photon emission computed tomography has shown reductions of dopamine transporter binding in the striatum (Riikonen et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Volume is not the sole attribute that can be measured of deep gray matter structures by using a variety of imaging methods. Magnetic resonance spectroscopy studies have reported altered brain metabolism in the thalamus (Fagerlund et al., 2006), striatum (Goncalves Rde et al., 2009), and caudate (Cortese et al., 2006) in FASD. Positron emission tomography revealed decreases in regional cerebral metabolic rates in bilateral thalamus and basal ganglia, which includes the caudate, putamen, and globus pallidus, in individuals with FAS (Clark et al., 2000) and single‐photon emission computed tomography has shown reductions of dopamine transporter binding in the striatum (Riikonen et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A third 1 H-MRS study reported decreased choline, a marker of phospholipid membrane turnover and myelination, in frontal/parietal white matter of preadolescent children with diagnosed FASD ( n = 20) compared with non-impaired children ( n = 61; Astley et al 2009). A second study reported decreased choline in the left striatum of children with FASD ( n = 8) when compared to controls (Goncalves Rde et al 2009). Finally, a more recent study which assessed young children with heavy alcohol exposure ( n = 37) and non- or minimally exposed controls ( n = 17), found several 1 H-MRS relationships within the cerebellum; decreased NAA was related to increased maternal use of alcohol around time of conception, decreased choline was related to higher levels of alcohol consumption during pregnancy, and alcohol consumption around time of conception and during pregnancy were related to increased glutamate with glutamine (Glx) (du Plessis et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…As reported among Astley et al's secondary findings, Cho also decreased with increasing amount of PAE across subjects. Gonçalves et al () found a below‐normal ratio of Cho to creatine + phosphocreatine (“Cho/Cr + PCr”) in an MRS acquisition volume (“voxel”) containing the internal capsule—the ventral extension of the corona radiata—as well as the putamen and caudate. Thus, there are indications of a possible role of ACR Cho in FASD.…”
Section: Introductionmentioning
confidence: 99%